Field tunable spin switching in perovskite YbFeO3 single crystal - Ma, Xiaoxuan; Yuan, Ning; Luo, Xiong; Chen, Yunke; Kang, Baojuan; Ren, Wei; Zhang, Jincang; Cao, Shixun (Materials today. Communications, 2021)
We report the spin reorientation transition and spin switching transition in perovskite structure YbFeO3 single crystal. A spin reorientation transition of type Г4→Г2 occurs in the temperature range of 6 ∼ 8 K, and a type-Ⅱ spin switching along c-axis is found at temperature about 20 K under an applied magnetic field of 100 Oe. In field-cooled-cooling (FCC) process, due to the spin reversal of Yb3+ magnetic moments, the magnetic moments coupling of Yb3+ and Fe3+ change from parallel to antiparallel, which leads to a significant drop in magnetization at the transition temperature. Interestingly, the Magnetization vs. magnetic field curves at various temperatures above 8 K-200 K show magnetic field induced spin switching, for which the magnetization switches from negative/positive value to positive/negative value but without change of magnitude at a magnetic field induced spin switching point. The intriguing interaction between the two magnetic sublattices of rare earth (Yb3+) and iron (Fe3+) ions is controllable by the applied magnetic field to regulate the spin switching transition temperature in YbFeO3 single crystal and make it possible as one of low field potential materials for future application in spin devices.